Pengaruh Discovery Learning berstrategi Kuantum untuk Meningkatkan Kemampuan Komunikasi Matematis dan Minat Belajar Siswa - suhirwah, suci ulfah; maulana, Maulana; Jayadinata, Asep Kurnia (Jurnal Pena Ilmiah, 2019)
Mathematics communication and student’s wiliing for learning is a focus of mathematical learning that important to grow in elementary school. Discovery learning with quantum strategy is the one of best alternative to increase mathematical communication skills and student’s willing for learning. The purpose of this research is to compare learning with discovery learning method with learning that use konventional approach. Research method that use is quasi experiment with non-equivalent control group design. Research sample is 31 students and 32 students. SDN Cintaasih I as experiment class and SDN Cintaasih II as control class. Result of the research shows that there were differences in the influence between discovery learning with quantum strategy with conventional approach for student’s mathematical communication skills and student’s willing for learning. The biggest influence is on class by discovery learning with quantum strategy. In other way, there is a positive connection between mathematical communication and studen’s willing for learning, with a contribution rate of 20,79%.